(untitled) (Raparin Journal of Humanities (RJH), 2020)
The legislative competence is considered to be the core of the parliamentary function, and considered as the most prominent competence of the legislative power, however the principle of the functional independence or the independence of the legislative power in practicing it’s role is not absolute because adjusting the progress of administration requires a kind of connection between the powers that led to the cooperation without override or infringement of the competences. Therefore, the Executive power of the Kurdistan region-Iraq is a main participant in legislative process; furthermore, it became the actual legislator in the comparing systems